Corporate taxes and labor market informality evidence from China - Deng, Guoying; Du, Pengcheng; Hernandez, Manuel A.; Xu, Shu (International Food Policy Research Institute, 2024)
This paper examines the association between corporate income taxes and labor market informality. We present a theoretical framework showing that a higher tax enforcement can push firms to pass on the burden to workers by reducing their social security compliance as well as downsizing and lowering wages. The model propositions are tested using a regression discontinuity design that exploits a national corporate tax reform in China. We find that for every one percentage point increase in the effective tax rate, firms reduce their probability of making basic social security contributions by 0.8%, their compliance rate by 1.4 percentage points, and the probability of making supplementary contributions by 0.6%, while the number of workers and wages fall by 4.4% and 0.7%, respectively. We observe that the effects are more salient among firms privately owned and controlled, large businesses, and in locations where social security contributions are directly collected by the social security administration. The findings suggest that workers not only bear part of the higher corporate taxes faced by firms, but an increase in firms’ tax burden contributes to social security evasion and informality in labor markets.